Outcome Measurements Used in Randomized Controlled Trials of Teledermatology: A Systematic Mapping Review - Aloysius Chow (Acta Dermato-Venereologica, 2019)

(untitled)
Assessment of the effectiveness of teledermatology has been hampered by the variety of outcome measures used, limiting the possibility for meta-analysis. This systematic mapping review classified the outcome measurement instruments used in randomized controlled trials of teledermatology conducted between 2008 and 2018 using the Core Outcome Measures in Effectiveness Trials taxonomy. Sixteen articles describing 12 studies were identified. Each trial used a mean of 3.7 outcome measurements (range 2–7) , with a total of 55 different instruments employed. Most instruments mapped on the “skin and subcutaneous tissue outcomes” domain. The most frequently used instrument (Dermatology Life Quality Index) was used in only 3 studies. Over 60% of the instruments used did not cite any evidence of validation. This mapping review provides a list of outcome measurement instruments that can be used as a resource when designing teledermatology trials in the future and provides the foundation for the development of a core outcome set.